The web 2.0 tools in the academic libraries: the Puerto Rico case - Camacho Camacho, Gerinaldo (2015)
The adoption of 2.0 technologies in academic library websites have become one of the primary forms of providing information services for their users. This study focused on exploring the presence of web 2.0 tools in the puertorrican academic libraries websites. A content analysis technique was use to evaluate 29 of the most important academic library website of the region. The results indicated that most academic libraries in Puerto Rico uses at least one or more web 2.0 tools in their website. The results also point out the blogs and social networks as the tools with the most presence. The researcher foresees that the academic libraries of Puerto Rico will integrate more web 2.0 tools applications in the near future. This study is useful for future planning and development of web 2.0 services for academic libraries.